ALMA-JELLY. I. High Resolution CO(2–1) Observations of Ongoing Ram Pressure Stripping in NGC 4858 Reveal Asymmetrical Gas Tail Formation and Fallback - Harrison J. Souchereau; Jeffrey D. P. Kenney; Pavel Jáchym; Ming Sun; William J. Cramer; Masafumi Yagi; Alessandro Boselli; Elias Brinks; Francoise Combes; Luca Cortese; Boris Deshev; Matteo Fossati; et al. (The Astrophysical Journal, 2025)
We present new CO(2–1) observations (resolution ∼1″ = 460 pc) of the Coma cluster jellyfish galaxy NGC 4858 obtained from the ALMA-JELLY large program. Analyzing this data alongside complimentary Subaru H α and Hubble Space Telescope (F600LP / F350LP) observations, we find numerous structural and kinematic features indicative of the effects from strong, inclined ram pressure, including an asymmetric inner gas tail. We estimate a highly inclined disk-wind angle of ${φ }_{\,\rm{DW}\,}=7{5}_{-27}^{+10}$ . By subtracting a simple circular velocity model, we find (1): gas clumps that are being accelerated by ram pressure, and (2): signatures of gas clumps that had been previously pushed out of the disk but are now falling inward. We also discuss head-tail morphologies in star complexes within the stellar disk that appear to be ram pressure stripping (RPS)-influenced. Lastly, we compare this galaxy to state-of-the-art galaxy “wind tunnel” simulations. We find that this galaxy is one of the best nearby examples of strong and inclined ram pressure gas stripping, and of gas that is perturbed by ram pressure but not fully stripped and falls back. We emphasize the importance of torques due to ram pressure in highly inclined interactions, which help drive gas inward on the side rotating against the wind, contributing to the formation of asymmetric inner RPS tails.